The main directions of the foreign policy of the First Prime Minister of the First Republic of Armenia Hovhannes Kajaznuni - Petrosyan, Gegham (YSU Journal of International Affairs, 2021)
The article covers in detail the main directions, priorities of the implementation of the country's foreign policy strategy presented in the draft program of the interim government of the First Republic of Armenia, presented in the first sittings of the parliament, the difficulties of overcoming them. Special attention was paid to the approaches and comments of the Prime Minister Hovhannes Kajaznuni on the external orientations of the Republic of Armenia set forth in the manuscript of the above-mentioned program, which were not published at the sittings.
Keywords: Republic of Armenia; Ottoman Turkey; Russia; England; Germany; Georgia; Azerbaijan; Interim Government of Armenia; Hovhannes Kajaznuni; Avetik Sahakyan; Meeting of the Council of Armenia